UTILIZATION OF LEARNING MANAGEMENT SYSTEM IN HIGHER EDUCATION INSTITUTION IN ENHANCING TEACHING AND LEARNING PROCESS - Azlim, Mastura; Husain, Kalthom; Hussin, Burairah; Maksom, Zulisman (Journal of Human Capital Development (JHCD), 2014)
Learning Management System (LMS) usage help learning process to be more active and productive. However, instructors are not stimulated to use the LMS optimally in their teaching environment. This study was conducted to identify the utilization of LMS in a public higher education institution in Malaysia among instructors. This quantitative approach study, adopts mail questionnaire to 93 instructors at higher education institution. The tools in LMS examined were Groups, Chat, Forum, Announcement, Document, Wiki, Learning Path, Users, Exercises, Course description and Agenda. The result shows low percentages of utilization of LMS from instructors even though they have positive perception towards the potential of LMS in enhancing teaching and learning process. Besides, the study also found that instructors were not exposed much on usage of the tools in LMS. Hence, a suggested LMS framework will be constructed to provide guidance to instructors. Keywords: Learning Management System (LMS), tools, utilization, learning process